Lintasan Belajar Materi Bangun Ruang Sisi Lengkung Dengan Pendekatan Pendidikan Matematika Realistik Dan Pembelajaran Kontekstual - Sarida Pulungan; Lisa Anggeraini; Ellis Mardianan Panggabean; Tua Halomoan Harahap (Hikamatzu | Journal of Multidisciplinary, 2025)
This study aims to develop a learning trajectory for the topic of curved-surface three-dimensional shapes (e.g., cylinders, cones, and spheres) using the Realistic Mathematics Education (RME) approach and Contextual Teaching and Learning (CTL). The abstract nature of geometric concepts often poses challenges for students, necessitating innovative teaching methods that connect mathematical concepts to real-world contexts. RME emphasizes the use of contextual problems as a starting point for learning, enabling students to construct mathematical knowledge through meaningful experiences. Meanwhile, CTL focuses on linking learning material to students' social, cultural, and environmental contexts, fostering deeper understanding and application of knowledge. By integrating these approaches, this research seeks to design a structured learning trajectory that guides students from basic conceptual understanding to complex problem-solving. The study also explores the impact of this trajectory on students' motivation, engagement, and conceptual mastery. Through a combination of qualitative and quantitative methods, the research examines the effectiveness of the proposed learning trajectory in improving students' mathematical reasoning and spatial visualization skills. The findings are expected to contribute to the development of more effective and contextually relevant mathematics teaching strategies, particularly in the area of geometry, and provide insights for educators and researchers in enhancing mathematics education..